1991
DOI: 10.1017/s0022215100116500
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the temporalis fascia

Abstract: The anatomy of the different layers of the temporalis fascia is reviewed. The superficial and deep layers of the temporalis fascia have been studied by light microscopy to assess any histological difference between the two. We have also assessed the physical characteristics of the different layers by measuring their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…Here, the attachment is so strong that removal of the fascia was only possible with the aid of a knife. This description of fascial attachment onto the arch agrees with Wormald and Alun-Jones (1991). It is this deep temporal fascia that was modeled in the finite element simulations.…”
Section: Results Dissectionssupporting
confidence: 74%
See 1 more Smart Citation
“…Here, the attachment is so strong that removal of the fascia was only possible with the aid of a knife. This description of fascial attachment onto the arch agrees with Wormald and Alun-Jones (1991). It is this deep temporal fascia that was modeled in the finite element simulations.…”
Section: Results Dissectionssupporting
confidence: 74%
“…The septal cartilage, which stretches from the perpendicular plate of the ethmoid to the external nose, may play some role in transmitting and dampening masticatory loads (Al Dayeh et al, 2009). Another potentially important external structure is the deep temporal fascia, which originates from the periosteum of the superior temporal line and attaches strongly to the superior border and lateral surface of the zygomatic arch (Eisenberg and Brodie, 1965;Wormald and Alun-Jones, 1991;Oxnard and Franklin, 2008). It has been suggested that the fasciae aid the zygomatic arch in resisting the tensions of the masseter muscle, which may be large during forceful biting (Eisenberg and Brodie, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…After autopsy, the fresh tissues were carefully dissected into muscle, tendon and fascia. The deep temporal fascia closely covers the temporalis muscle and its aponeurosis follows the muscle's anatomical boundaries (Wormald and Alun-Jones, 1991). The muscle fibers were thoughtfully removed from the deep temporal fascia and temporal tendon using the back of the scalpel, avoiding damage to the underlying fascia, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The temporal muscle enables elevation and retraction of the mandible, thus its overstimulation leads to recurrent temporal headaches. The connective tissue of the temporal fascia (Wormald and Alun-Jones, 1991) allows some amount of shear deformation to occur between the muscle and the fascia in such a way they can ''glide'' past one another. The temporal tendon is a roughly uniaxial composite made of mainly type I collagen fibers that connects the temporal muscle to the coronoid process (Gray and Lewis, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The so-called "temporal fascia" in mammals represents a "two-layer structure," including a deep and a superficial layer (e.g., Wormald and Alun-Jones, 1991;Campiglio and Candiani, 1997). The deep layer is associated to the m. temporalis, and hence corresponds to the fascia(e) of the nervus trigeminus innervated jaw muscles (m. adductor mandibulae complex; see below).…”
Section: Further Tendinous Structures Of the Craniummentioning
confidence: 99%